Effectiveness and use of reverse transcriptase polymerase chain reaction point of care testing in a large‐scale COVID‐19 surveillance system. Issue 5 (11th March 2022) - Mack, Christina D.; Wasserman, Erin B.; Hostler, Christopher J.; Solomon, Gary; Anderson, Deverick J.; Walton, Patti; Hawaldar, Kalyani; Myers, Emily; Best, Michele; Eichner, Daniel; Mayer, Thom; Sills, Allen
Abstract: Background: Rapid COVID‐19 testing platforms can identify infected individuals at the point of care (POC), allowing immediate isolation of infected individuals and reducing the risk of transmission. While lab‐based nucleic acid amplification testing (NAAT) is often considered the gold standard to detect SARS‐CoV‐2 in the community, results typically take 2–7 days to return, rendering POC testing a critical diagnostic tool for infection control. The National Football League (NFL) and NFL Players Association deployed a new POC testing strategy using a newly available reverse transcriptase polymerase chain reaction (RT‐PCR) rapid test during the 2020 season, and evaluated diagnostic effectiveness compared to other available devices using real‐world population surveillance data. Methods: RT‐PCR POC test results were compared to NAAT results from same‐day samples by calculation of positive and negative concordance. Sensitivity analyses were performed for three subgroups: (1) individuals symptomatic at time of positive test; (2) individuals tested during the pilot phase of rollout; and (3) individuals tested daily. Results: Among 4989 same‐day POC/NAAT pairs, 4957 (99.4%) were concordant, with 93.1% positive concordance and 99.6% negative concordance. Based on adjudicated case status, the false negative rate was 0.2% and false positive rate was 2.9%. In 43 instances, the immediate turnaround of results by POC allowed isolation of infected individuals 1 day sooner than lab‐based testing. Positive/negative concordance in sensitivity analyses were relatively stable. Conclusion: RT‐PCR POC testing provided timely results that were highly concordant with lab‐based NAAT in population surveillance. Expanded use of effective RT‐PCR POC can enable rapid isolation of infected individuals and reduce COVID‐19 infection in the community.